2010
DOI: 10.1063/1.3340909
|View full text |Cite
|
Sign up to set email alerts
|

Observation of runaway electron beams by visible color camera in the Experimental Advanced Superconducting Tokamak

Abstract: The synchrotron radiation originated from the energetic runaway electrons has been measured by a visible complementary metal oxide semiconductor camera working in the wavelength ranges of 380-750 nm in the Experimental Advanced Superconducting Tokamak [H. Q. Liu et al., Plasma Phys. Contr. Fusion 49, 995 (2007)]. With a tangential viewing into the plasma in the direction of electron approach on the equatorial plane, the synchrotron radiation from the energetic runaway electrons was measured in full poloidal cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…(53) and 50cm, respectively. The toroidal magnetic fields of these three tokamaks are about 5T , 2T and 2T [30][31][32]. The estimation of d 2 ∼ 26cm is comparable to any minor radii listed above.…”
Section: Phase-space Dynamics Of Runaway Electronssupporting
confidence: 49%
“…(53) and 50cm, respectively. The toroidal magnetic fields of these three tokamaks are about 5T , 2T and 2T [30][31][32]. The estimation of d 2 ∼ 26cm is comparable to any minor radii listed above.…”
Section: Phase-space Dynamics Of Runaway Electronssupporting
confidence: 49%
“…A similar shape was observed in visible light for startup runaways in EAST. 11 In shot 146704 shown in Fig. 6, an unknown instability (which occurs after the time shown in the figure) causes the crescent to suddenly change to an oval shape on a timescale of approximately 100 ls.…”
Section: Runaway Images In the Visible Spectral Regionmentioning
confidence: 98%
“…7 REs have been studied previously on a number of tokamaks. 8 Imaging in particular was a key diagnostic in the following cases: during massive gas injection (MGI) experiments using IR synchrotron emission at TEXTOR, 9,10 during plasma startup using visible synchrotron emission at EAST, 11 and during disruptions using soft x-ray (SXR) tomography at JET 12 and using visible emission at HL-2A. 13 Here, we present the first visible light images of synchrotron emission from REs generated during Ar pellet-induced disruptions in DIII-D, 14 and we show visible spectra during the RE current plateau.…”
Section: Introductionmentioning
confidence: 99%
“…While this approach has been applied with considerable success [8], it has been demonstrated that multiple distributions can be fit to a single spectrum [9]. In an effort to provide additional constraints to the distribution function, filtered 2D visible imaging has been employed on multiple devices [4,7,[10][11][12][13][14][15]. The downside of using camera images is the loss of spectral information.…”
Section: Introductionmentioning
confidence: 99%